Effect of gender specific anthropometric characteristics on lung function in young competitive triathletes from Malaysia - Johari, H. M.; Zainudin, H. A.; Knight, V. F.; Lumley, S. A.; Subramanium, S.; Caszo, B. A.; Gnanou, J. V. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Anthropometric and lung function characteristics of triathletes are important for the implementation of individual specific training and recovery recommendations. However, limited data are available for these parameters in triathletes. Hence, the aim of this study was to characterize and examine the gender differences of lung function and anthropometry parameters in competitive triathletes from Malaysia.